2013
DOI: 10.1039/c3dt33046j
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo activity of a new unsymmetrical dinuclear copper complex containing a derivative ligand of 1,4,7-triazacyclononane: catalytic promiscuity of [Cu2(L)Cl3]

Abstract: Here we present the synthesis of the dinuclear complex [Cu(II)2(L)Cl3] (1), where L is the deprotonated form of the 3-[(4,7-diisopropyl-1,4,7-triazacyclononan-1-yl)methyl]-2-hydroxy-5-methylbenzaldehyde ligand. The complex was characterized by single crystal X-ray diffraction, potentiometric titration, mass spectrometry, electrochemical and magnetic measurements, EPR, UV-Vis and IR. Complex 1 is able to increase the hydrolysis rate of the diester bis-(2,4-dinitrophenyl)phosphate (2,4-BDNPP) by a factor of 2700… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 67 publications
(73 reference statements)
1
5
0
Order By: Relevance
“…In order to evaluate the kinetic profile of cleavage of complex 1 (Figure ), a pseudo-Michaelis–Menten analysis was performed and the obtained parameters are shown in Table . This indicates that complex 1 cleaves DNA with a k cat value of 0.89 h –1 and an enhancement over the uncatalyzed DNA cleavage reaction of 2.4 × 10 7 times; these data are consistent with the literature. …”
supporting
confidence: 89%
“…In order to evaluate the kinetic profile of cleavage of complex 1 (Figure ), a pseudo-Michaelis–Menten analysis was performed and the obtained parameters are shown in Table . This indicates that complex 1 cleaves DNA with a k cat value of 0.89 h –1 and an enhancement over the uncatalyzed DNA cleavage reaction of 2.4 × 10 7 times; these data are consistent with the literature. …”
supporting
confidence: 89%
“…The (3-[(4,7-diisopropyl-1,4,7-triazacyclononan-1-yl)methyl]-2hydroxy-5-methylbenz-aldehyde), labeled Cmff-TACN, was synthesized according to the literature. 36 Agarose was obtained from Invitrogen™. Bluescript SK II Plasmid DNA ( pBSK II) (2961 bp) was purchased from Stratagene (USA), HiSpeed Plasmid Purification Kit was purchased from QIAGEN, and Acetonitrile HPLC grade was purchased from TediaBrasil.…”
Section: Methodsmentioning
confidence: 99%
“…26,27 Thorough literature search revealed that heterocycles containing an N-donor atom ring system, such as 1,4,8,11-tetraazacyclotetradecane (cyclam), 28 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA) 29 and 1,4,7-triazacyclononane (TACN), 30 exhibit a wide spectrum of medical and biomimetical activities, for example, acting as a chelator for image contrast, 31,32 nucleic acids delivery, 33 DNA cleavage 34 or therapeutic agents for cancer. 35,36 By considering the biological significance of these two classes of molecules, it was contemplated to construct new triazacyclononane-substituted porphyrins combining the porphyrin and TACN moieties, using 2-chloromethyl-4-methyl-6-formylphenol (Cmff ) as a spacer, in a single molecular framework. Such hybrid compounds can be a potential candidate of new phototherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, several other classes of 64 Cu­[Cu II ] chelators have been identified as suitable agents for PET. ,,, Macrocyclic polyaminocarboxylates derived from cross-bridged (CB) cyclam provide impressive thermodynamic and kinetic stability through the constrained binding cavity; ,, however, these systems can require harsh and extended radiolabeling conditions incompatible with biological conjugating agents , without further modification. Frameworks based on 1,4,7-triazacyclononane (tacn; e.g., NOTA) can display excellent stability and chelate 64 Cu­[Cu II ] rapidly under mild conditions, ,,, while further modifications to molecular charge, lipophilicity, and conjugation can lead to improved performance. ,, Pre-organized polycyclic N -donor chelates based on bispidine (bispa) and sarcophagi (SarAr) scaffolds can enable mild radiolabeling conditions and reasonable in vivo stability. Functionalization can be low yielding due to unselective alkylation and the presence of multiple regioisomers; however, several effective approaches have been identified and clinical trials are ongoing. , , …”
Section: Introductionmentioning
confidence: 99%